Strategi Pemasaran Digital Pada PT. Setiabudi Persada Sukabumi - Hendra Ningsih, Ratih; Farida Utami, Sri; Liliawati, Lia (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
A house is one of the basic needs of humans, it will definitely meet its basic needs, as well as a place to live. This research is to find out the Digital Marketing Strategy at PT. Setiabudi Persada, Sukabumi Regency in marketing Setiabudi Estate housing as well as the obstacles faced and solutions that have been carried out. The Digital Marketing Strategy used in this study is Market Segmentation (Segmenting), Target Market (Targeting), and Market Positioning (Positioning) as well as the stages of digital marketing. The research method used by the author in writing the Final Project report is a descriptive qualitative method by analyzing data on PT. Setiabudi Persada Sukabumi Regency is seen from Market Segmentation (Segmenting), Target Market (Targeting), and Market Position (Positioning). The data collection techniques in this study include interview methods, observation methods and literature methods. The results of the research from Marketing Strategy at PT. Setiabudi Persada of Sukabumi Regency stated that market segmentation (Segmenting) with consumers who have behavior in harmony with the nature of Sukabumi is also with a modern and practical lifestyle, Target market (Targeting) with the target market prioritized for permanent employees, Market Positioning (Positioning) as urban living housing with a modern minimalist style using the current market and considering air health. Then the stages of digital marketing carried out are market research, branding development, creative content, Social Media Marketing, paid advertising sponsorship, SEO optimization and email marketing.